Kombuistaal innie Kaap1: Investigating Gender and Language Change in the development of Kaaps - Thornton, Lizanne (Linguistics, 2024)
This thesis asks the question: How have women contributed to the maintenance of Kaaps? It takes as its point of departure the term kombuistaal (kitchen language), the forerunner of Kaaps, a stigmatised variety of Afrikaans. It aims to answer the following supplementary questions: 1) What possible role did women who occupied spaces historically associated with the Cape slave kitchen of the seventeenth to early nineteenth century play in language maintenance? 2) How do we go beyond the written records of the traditional archive and listen for the muted voices of those language pioneers who, by virtue of particular social and gendering processes, were uniquely placed to develop and maintain the language which has come to be known as Kaaps? By means of a historical sociolinguistic approach with a qualitative method of thematic narrative analysis, the study argues that women's historical contribution to the development of Kaaps has been underplayed and marginalised by virtue of the relegated social status effected through imposed gendered roles and enforced labour in specific and often largely invisible spaces of cultural reproduction. With a focus on language change and maintenance of Kaaps through a gendered lens, this study aims to highlight the contributions of Kaaps speakers who, by virtue of their gendered social positioning, became inextricably linked to a language which has been historically associated with the space of the kitchen.